Pre‐ and post‐natal Lactobacillus reuteri supplementation decreases allergen responsiveness in infancy. Issue 4 (21st March 2013) - Forsberg, A.; Abrahamsson, T. R.; Björkstén, B.; Jenmalm, M. C.
Summary Background We have previously shown that Lactobacillus reuteri supplementation from pregnancy week 36 and to the infant through the first year of life decreased the prevalence of IgE‐associated eczema at 2 years. The underlying immunological mechanisms are unknown, however. Objective To investigate the immunomodulatory effect of probiotic supplementation on allergen‐ and mitogen‐induced immune responses in children until 2 years of age. Methods Blood mononuclear cells were collected at birth, 6, 12 and 24 months from 61 children (29 probiotic and 32 placebo treated) and cultured with ovalbumin, birch and cat extract and Phytohaemagglutinin (PHA). Cytokine and chemokine secretion was determined using an in‐house multiplexed Luminex assay and ELISA. Real‐time PCR was performed to investigate the Ebi3, Foxp3, GATA‐3 and T‐bet mRNA expression. Results Probiotic treatment was associated with low cat‐induced Th2‐like responses at 6 months (IL‐5, P = 0.01, and IL‐13, P = 0.009), with a similar trend for IL‐5 at 12 months (P = 0.09). Cat‐induced IFN‐γ responses were also lower after probiotic than after placebo treatment at 24 months (P = 0.007), with similar findings for the anti‐inflammatory IL‐10 at birth (P = 0.001) and at 12 months (P = 0.009). At 24 months, Th2‐associated CCL22 levels were lower in the probiotic than in the placebo group after birch stimulation (P = 0.02), with a similar trend after ovalbumin stimulation (P = 0.07). Lower CCL22 levels were recorded at 12 and 24 months (P = 0.03 and P = 0.01) after PHA stimulation. Conclusion and Clinical Relevance Lactobacillus reuteri supplementation decreases allergen responsiveness and may enhance immunoregulatory capacity during infancy. L. reuteri supplementation from week 36 and during the first year of life significantly decreases IgE‐associated eczema and lowers allergen and mitogen responsiveness.